Super trooper. - Koh, Jason Thiam Joo. (2010)
Super Trooper is a photo book that delves into the lives of several Star Wars fans in Singapore through studio portraiture and personality interviews. These fans, all part of 501st Legion's Singapore Garrison, dress up as Star Wars characters for charity.